GLUCOSE-INDUCED LIPID DEPOSITION IN GOOSE PRIMARY HEPATOCYTES IS DEPENDENT ON THE PI3K-Akt-mTOR SIGNALING PATHWAY - Han, Chunchun; We, Shouhai; He, Fang; Song, Qi; Xiong, Xiangping; Ye, Fengjiang; Liu, Dandan; Wan, Huofu; Liu, Hehe; Li, Liang; Xu, Hongyong; Xu, Feng; et al. (Archives of Biological Sciences, 2016)
Previously we showed that fatty liver formation in overfed geese was accompanied by PI3K-Akt-mTOR pathway activation and changes in plasma glucose concentrations. Here, we show that glucose acts in goose hepatocellular lipid metabolism through the PI3K-Akt-mTOR signaling pathway. We observed that glucose increased lipogenesis, decreased fatty acid oxidation and increased very low density lipoprotein triglyceride (VLDL-TG) assembly and secretion. Co-treatment with glucose and inhibitors of the PI3K-Akt-mTOR pathway (LY294002, rapamycin, NVP-BEZ235) decreased the levels of factors involved in lipogenesis and increased the levels of factors involved in fatty acid oxidation and VLDL-TG assembly and secretion. These findings show that inhibition of the PI3K-Akt-mTOR pathway decreased glucose-induced lipogenesis, inhibited the downregulation of fatty acid oxidation by glucose and increased the upregulation of VLDL-TG assembly and secretion by glucose. The results presented herein provide further support for the role of the PI3K-Akt-mTOR pathway in lipid metabolism as we showed that in goose primary hepatocytes, glucose acts through the PI3K-Akt-mTOR-dependent pathway to stimulate lipid deposition by increasing lipogenesis and decreasing fatty acid oxidation and VLDL-TG assembly and secretion. DOI: 10.2298/ABS151210075H Key words: glucose; PI3K-Akt-mTOR pathway; lipogenesis; fatty acid oxidation; VLDL assembly and secretion Received: December 10, 2015; Revised: January 15; Accepted: January 16, 2016; Published online: August 19, 2016 How to cite this article: Han C, We S, He F, Qi S, Xiong X, Ye F, Liu D, Wan H, Liu H, Li L, Xu H, Xu F, Zeng X. Glucose-induced lipid deposition in goose primary hepatocytes is dependent on the PI3K-Akt-mTOR signaling pathway. Arch Biol Sci. 2016;68(4):853-61.